Aplikasi Manajemen Data Siswa dan Nilai Berbasis Android Menggunakan Flutter dan Firebase dengan Metode Waterfall - Setiawan, Chandra Bagus; Rusliyawati, Rusliyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of information technology has brought significant changes to the education sector, particularly in the management of academic data. Manual processing of student data and grades often leads to various issues, such as delayed input, recording errors, and a lack of transparency for students. To address these problems, this study aims to design and develop an Android-based Student and Grade Management Application that improves efficiency and accuracy in academic data management within schools. The application is built using the Flutter framework and utilizes Firebase Realtime Database as a cloud-based storage system. The development process follows the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance. System testing is carried out using the Black Box method to ensure that all features function as intended. The testing results show a success rate of 98%, indicating that the application performs well according to the design specifications. The implementation of this application helps teachers manage grades more quickly and accurately, while allowing students to access academic information in real time. Overall, the application supports the digital transformation of schools and promotes the adoption of paperless school practices.